2018
DOI: 10.1038/s41598-018-30469-8
|View full text |Cite
|
Sign up to set email alerts
|

On detection of periodicity in C-reactive protein (CRP) levels

Abstract: C-reactive protein (CRP) is an acute-phase plasma protein that can be used as a biomarker for activation of the immune system. A spectral analysis of CRP level over time for patients with gynaecological tumours has been reported by Madondo et al., using a periodogram method, suggesting that there is no significant periodicity in the data. In our study, we investigate the impact of low sample number on periodogram analysis, for non-uniform sampling intervals—we conclude that data of Madondo et al. cannot rule o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In summary, the circaseptan (7-day ± 1-day) periodicity pattern described, in some cases accompanied by other infradian cycles, such as a hemicircaseptan cycle, is robust in large and reliably reporting countries representing Europe (Italy; Germany, Sweden, United Kingdom), Asia (Japan, South Korea), and North (the United States) and South (Brazil) America, as well as in the whole world. Understanding the relationship between variables associated with the observed periodicities might help in health care improvements, better forecasting of the coronavirus infection, and stock market expectations about economic growth and might help provide a clue for the most suitable times at which expected COVID-19 therapies should be administered ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the circaseptan (7-day ± 1-day) periodicity pattern described, in some cases accompanied by other infradian cycles, such as a hemicircaseptan cycle, is robust in large and reliably reporting countries representing Europe (Italy; Germany, Sweden, United Kingdom), Asia (Japan, South Korea), and North (the United States) and South (Brazil) America, as well as in the whole world. Understanding the relationship between variables associated with the observed periodicities might help in health care improvements, better forecasting of the coronavirus infection, and stock market expectations about economic growth and might help provide a clue for the most suitable times at which expected COVID-19 therapies should be administered ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of immune therapies or cytotoxic chemotherapies to the oscillating and fluctuating immune system occurring in the individual patient presents a significant problem if the action of the specific agent depends on precisely when the agent is administered with reference to the phase of activation or inhibition of the immune system at the time. Recent work has been unable to accurately define the periodicity of the immune oscillation in cancer patients despite initial work using less robust mathematics appearing to show this [139][140][141][142] . Advanced mathematics and periodicity models have been incapable of verifying regular, consistent, clear, regular immune cycles, principally due to infrequent inflammatory marker serial sampling and confounding noise-to-signal issues, but machine (deep) learning may offer alternative methods.…”
Section: Anti-cancer Agents and Immune Responsesmentioning
confidence: 99%
“…Besides, the association between prognosis and CRP levels in patients with cancer is currently well established. In particular, CRP is extensively reported in oncology as a reliable biomarker for survival, cancer risks, and tumor recurrence, impacting on many critical decisions in treatment [20]. Moreover, recent clinical and epidemiological studies have demonstrated the association between inflammation and cardiovascular diseases [21].…”
Section: Introductionmentioning
confidence: 99%